2019
DOI: 10.1111/1744-9987.12807
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis Product and Hip Fracture in Hemodialysis Patients: A Nationwide Cohort Study in Japan

Abstract: Some have raised concerns that longer and more frequent hemodialysis (HD) would be associated with bone fractures due to excess phosphate removal. We examined the effects of hemodialysis product (HDP) on hip fracture incidence among Japanese HD patients using registry data of the Japanese Society for Dialysis Therapy. During a 1‐year study period, 1411 hip fractures occurred among 135 984 patients. After adjusting for demographic and clinical factors, patients with a high HDP did not show a significant risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A low albumin level is reportedly one of many factors associated with fractures [ 18 ], while an association between a low BMI and fractures remains controversial. One previous study showed that a low BMI is significantly associated with fractures [ 18 ], although other studies found no such association [ 3 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A low albumin level is reportedly one of many factors associated with fractures [ 18 ], while an association between a low BMI and fractures remains controversial. One previous study showed that a low BMI is significantly associated with fractures [ 18 ], although other studies found no such association [ 3 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that low serum albumin is associated with new fractures [ 10 ]. However, the association between a low BMI and fractures remains controversial [ 3 , 10 , 11 ]. We hypothesized that malnutrition is associated with fracture, and that the GNRI , as an indicator of malnutrition, can predict the risk of fractures.…”
Section: Introductionmentioning
confidence: 99%